Excessive television-viewing time and its influence on adolescent food intake - Enes, Carla Cristina; Lucchini, Beatriz Guerra [UNESP] (Pontificia Universidade Catolica Campinas, 2016)
Objective To investigate the association between television-viewing time and adolescent food intake. Methods This cross-sectional study included 815 male and female adolescents from public schools in Piracicaba, Sao Paulo. The following data were collected: sociodemographic and anthropometric data, television-viewing time, and habitual food intake. The latter was obtained by a food frequency questionnaire to assess the intake adequacy (servings/day) of seven food groups according to the Brazilian Food Guide. Television-viewing time regarded the total number of hours per day dedicated to watching television, which was then classified into two categories: <= 2 hours/day and >2 hours/day. The Student's t test measured the difference between the means of the continuous variables. The relationship between the independent variables and television-viewing time was tested by Poisson regression. Results Adolescents with higher television-viewing time consumed more milk and dairy products (p=0.03), sugars and sweets (p=0.01), and soda (p=0.02). Low fruit intake, high sweet, sugar, and soda intakes, and lower age were associated with higher television-viewing time. In multivariate analysis unhealthy food habits, such as low fruit intake (p=0.014) and high sugar and sweet intakes (p=0.041), remained independently associated with television-viewing time. Conclusion High television-viewing time was associated with poor eating habits. Adolescents with high television-viewing time should be encouraged to make healthier food choices, since poor eating habits and physical inactivity increase the risk of chronic diseases already during adolescence, especially when combined.
Keywords: Adolescent; Behavior; Food intake; Obesity; Television